Evaluating Flock Dynamics, Offtake-rate, and Farmers’ Perception on Benefits of Community Based Breeding Program in Doyogena District, Central Ethiopia - Jimma, Addisu; Melesse, Aberra; Haile, Aynalem; Getachew, Tesfaye (ResearchersLinks, 2024)
The community-based breeding program (CBBP) is currently active in implementing indigenous breed improvement strategies to achieve genetic progress, economic benefits, and livelihood improvements for smallholders in the pioneer sheep breed improvement cooperatives in Ethiopia. Although the Doyogena sheep CBBP is one of the well-performing breeding cooperatives, there is a lack of up-to-date information regarding farmer perspectives on morphological and reproductive changes (such as conformation, coat color, litter size, growth, and lambing interval), socio-economic benefits, off-take, flock structure, and trends since the CBBP started. To address this gap, a study involving 260 randomly selected farmers, with 130 being CBBP members and 130 non-members owning sheep from similar locations, was conducted. The results revealed significant differences (p<0.05) in various aspects between CBBP members and non-members. CBBP participants showed higher numbers of lambs below 3 months, male lambs between 3-6 months, intact males between 6-12 months, breeding rams, mature ewes, and the mean flock size of sheep at the household level. The major routes of sheep entry into the flocks were birth (81%), and purchase (17%). The total number of entries and births was higher (p < 0.05) in CBBP members (284 vs. 240) than in non-members (148 vs. 112). The off-take rate, representing the proportion of sheep exits from the flock, was significantly higher (p<0.05) in CBBP members (36.45%) compared to non-members (17.35%). Factors such as CBBP participation, gender of the household head, age, flock size, and farm land size influenced flock dynamics and off-take rates. The CBBP was attributed to performance improvements in traits such as growth, coat color, litter size, survival, and lambing interval. Moreover, the program had a positive influence on economic benefits, as CBBP members reported higher annual income from sheep-related activities. This income played a crucial role in supporting farmers’ livelihoods, contributing to house maintenance and providing food for households. In conclusion, the study highlights the positive influence of the Doyogena CBBP on farmers’ livelihoods, thus suggesting the need to scale up the program to benefit a broader community.